Asherman's Syndrome due to Endometrial Tuberculosis: A Case Report and Literature Review - Pratama, Anugerah Justi; Prabowo, Adityo; Tantular, Rezki; Fadli, M Luqman (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Female genital tuberculosis, a rare form of extrapulmonary TB, often goes underdiagnosed despite its potential to cause significant reproductive complications such as amenorrhea and infertility. The theory behind this case emphasizes the need for heightened awareness and improved diagnostic approaches to effectively manage endometrial TB and its associated intrauterine adhesions. Case Presentation: A 31-year-old woman presented with a four-year history of oligomenorrhea and 3.5 years of primary infertility, undergoing various treatments including hormone therapy and ultrasound evaluations that revealed intrauterine masses and cervical issues. Following a hysteroscopic surgery that identified cervical stenosis and a tuberculous mass, she was treated for endometrial tuberculosis with anti-tuberculosis medication. Despite treatment, she continued to experience abnormal menstrual cycles, leading to further hysteroscopic evaluations that indicated significant uterine fibrosis and chronic cervicitis. The patient declined the insertion of a levonorgestrel-releasing intrauterine system (LNG-IUS) but received a Depo Medroxy Progesterone Acetate (DMPA) injection and was fitted with an IUD, alongside hormonal therapy with cycloproginova, with ongoing assessments showing improvements in uterine vascularity and visibility of the fallopian tubes. Conclusion: This case highlights the complexities of managing secondary amenorrhoea due to genital tuberculosis, which disrupts endometrial function and results in significant intrauterine adhesions. A multidisciplinary approach, involving hysteroscopic adhesiolysis, anti-tubercular therapy, and postoperative hormonal interventions, is crucial for effective treatment. Despite the restoration of menstrual cycles, ongoing fertility risks and pregnancy complications necessitate thorough preconception counselling and long-term monitoring.